Agronomic effectiveness of rock phosphate in an andept of Ethiopia - Nnadi, L.A.; Haque, I. (Informa UK Limited, 1988)
Compares the relative agronomic effectiveness of Togo and Egypt rock phosphate sources with triple super phosphate on high fixing volcanic ash soil of Ethiopia using lucerne as indicator crop.